Megaprosthesis of the knee in tumor and revision surgery - Pala, E.; Trovarelli, G.; Angelini, A.; Maraldi, M.; Berizzi, A.; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2017)
The introduction of multidisciplinary approach with chemo and radiotherapy, the advances in surgical and the improvements of diagnostic techniques allowed limb salvage surgery in most cases of bone sarcomas instead of amputation. Modular megaprostheses are the most common method of reconstruction after segmental resection of the long bones in the extremities for their availability, immediate fixation, early weight bearing, good function. Despite the advances in materials and implant designs, these systems have an high incidence of complications. Aim of this study was to report the experience on mega-prostheses implanted around the knee in tumor and revision surgery to analyze: the most frequent used current systems, the problems of stems fixation, extensor mechanism reconstructions in proximal tibia resections and the preservation of growth of the lower extremity in children.